Jogos Educacionais Digitais Abertos Interdisciplinares: um estudo de caso com professores da rede pública do Estado de São Paulo - Tomceac, Jean Rafael (2013)
This research refers to a case study that used as the object Interdisciplinary Open Digital Educational Games (Jogos Educacionais Digitais Abertos Interdisciplinares - JEDAI) to prove whether teachers, who are little exposed this technology, have the ability to analyze and predict the pedagogical learning dimensions created in the game environment. It therefore supports the theoretical reference of Maria Helena Soares de Souza, Fernando José de Almeida, Maria da Graça de Silva and Monica M. Gardelli Franco to define the characteristics of JEDAI. Questionnaires have been used as instrument to collect the data and were answered by 75 participants (public school teachers of the state of São Paulo and participants of a thematic workshop). Of these 75 completed questionnaires, 28 were selected for further analysis and interpretation of data. The partial result of the research indicates how participants identify the pedagogical characteristics of the types of games covered here